Impact of Iron Deficiency on Cognition in School Age Children - Sitorus, Nova Lidia; Nuraeni Salsabila, Irma (Ridwan Institute, 2023)
Iron deficiency is a significant global health problem, especially among school children. Iron deficiency has a serious impact on children's health, including cognitive development. The aim of this study was to investigate the impact of iron deficiency on cognitive function of school-aged children. This study used a cross-sectional design. The study sample was school-aged children who met the inclusion criteria. The inclusion criteria were children aged 6-12 years, had hemoglobin <12 g/dL, and had no other chronic diseases. Exclusion criteria were children who were undergoing certain drug therapy, children who had other cognitive developmental disorders, and children who had a history of allergy to iron. Data were collected through interviews, physical examinations, and laboratory tests. Data were analyzed using descriptive statistical tests. The results showed that iron-deficient children had lower cognitive function than non-iron-deficient children. This is indicated by lower scores on cognitive tests, such as memory, attention, and learning ability tests. Therefore, it is important to prevent and treat iron deficiency in school-age children